Vision and Visuomotor Performance Following Acute Ischemic Stroke - Wijesundera, Chamini; Crewther, Sheila G.; Wijeratne, Tissa; Vingrys, Algis J. (Frontiers in Neurology, 2022)
Background: As measurable sensory and motor deficits are key to the diagnosis of stroke, we investigated the value of objective tablet-based vision and visuomotor capacity assessment in acute mild-moderate ischemic stroke (AIS) patients. Methods: Sixty AIS patients (65±14 years,33 males) without pre-existing visual/neurological disorders and acuity better than 6/12 were tested at their bedside during the first week poststroke and were compared to 40 controls (64±11 years,15 males). Visual field sensitivity, quantified as mean deviation (dB) and visual acuity (with and without luminance noise), were tested on MRFn (Melbourne Rapid Field-Neural) iPad application. Visuomotor capacity was assessed with the Lee-Ryan Eye-Hand Coordination (EHC) iPad application with a capacitive stylus for iPad held in the preferred hand. Time to trace shapes and displacement errors (deviations >3.5 mm from the shape) were recorded. Diagnostic capacity was considered with Receiver Operating Characteristics. Vision test outcomes were correlated with National Institutes of Health Stroke Scale (NIHSS) score at admission. Results: Of the 60 AIS patients, 58 grasped the iPad stylus in their preferred right hand even though 31 had left hemisphere lesions. Forty-one patients (68%) with better than 6/12 visual acuity (19 right, 19 left hemisphere, and 3 multi-territorial lesions) returned significantly abnormal visual fields. The stroke group took significantly longer (AIS:93.4  60.1s; Controls:33.1  11.5s, p<0.01) to complete EHC tracing and made larger displacements (AIS:16,388  36,367 mm;Controls:2,620  1,359 mm, p<0.01) although both control and stroke groups made similar numbers of errors. EHC time was not significantly different between participants with R (n=26, 84.3  55.3 s) and L (n=31, 101.364.7 s) hemisphere lesions. NIHSS scores and EHC measures showed low correlations (Spearman R: -0.15, L: 0.17). ROC analysis of EHC and vision tests found high diagnostic specificity (98%) and sensitivity (95%) for EHC time and visual field deviation (sensivity:92%,specificity:94%) that show little relationship to NIHSS scores. Conclusions: EHC time and vision test outcomes provide an easy and rapid bedside measure that complements existing clinical assessments in AIS. The low correlation between visual function, NIHSS scores, and lesion site offers an expanded clinical view of changes following stroke. Clinical Trial: ACTRN12618001111268